2017
DOI: 10.5194/acp-17-14887-2017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vernal equinox solar eclipse on temperature and wind direction in Switzerland

Abstract: Abstract. The vernal equinox total solar eclipse of 20 March 2015 produced a maximum occultation of 65.8-70.1 % over Switzerland during the morning hours (09:22 to 11:48 CET). Skies were generally clear over the Swiss Alps due to a persistent high-pressure band between the UK and Russia associated with a rather weak pressure gradient over the continent. To assess the effects of penumbral shading on near-surface meteorology across Switzerland, air temperature data measured at 10 min intervals at 184 MeteoSwiss … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…Similar near-surface thermal responses were also simulated by McInerney et al (2018). Second, the atmospheric pressure decreases due to the eclipse cyclone (Clayton, 1901;Eugster et al, 2017) in response to the rapid atmospheric cooling in the eclipse umbra. Pressure changes of 0.26-2.0 hPa have been observed (Anderson and Keefer, 1975;Aplin and Harrison, 2003;Eckermann et al, 2007;Aplin et al, 2016).…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Similar near-surface thermal responses were also simulated by McInerney et al (2018). Second, the atmospheric pressure decreases due to the eclipse cyclone (Clayton, 1901;Eugster et al, 2017) in response to the rapid atmospheric cooling in the eclipse umbra. Pressure changes of 0.26-2.0 hPa have been observed (Anderson and Keefer, 1975;Aplin and Harrison, 2003;Eckermann et al, 2007;Aplin et al, 2016).…”
Section: Introductionmentioning
confidence: 52%
“…First, the near-surface air temperature decreases. The magnitude of this temperature change and timelag between the minimum solar radiation and the local minimum temperature is site-and event-dependent (e.g., on latitude, surface characteristics, synoptic forcing, cloud coverage, and time-of-day and duration of totality of the eclipse event), with an observed temperature drop of 1.5-10 • C (Stewart and Rouse, 1974;Anderson and Keefer, 1975;Aplin and Harrison, 2003;Aplin et al, 2016;Eugster et al, 2017), and with 15-20 min lags (Antonia et al, 1979;Aplin et al, 2016). Similar near-surface thermal responses were also simulated by McInerney et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…We note that this average value is based on both partial and total solar eclipse events that occurred at various times throughout the day. Eugster et al [20] reported that the temperature reduction showed no dependence on eclipse type (partial vs. total), geographic location and several other factors. Additionally, the 5.0 • C recorded decrease is in line with other temperature measurements made across the continental United States by weather stations in the U.S.…”
Section: Radiosondesmentioning
confidence: 99%
“…A time lag between radiation changes and temperature response is visible in the main tower observations, with temperature decreasing following the decrease in radiation. The vertical temperature gradient at the main tower reversed at 14:06 EDT (35 min [20] compiled 130 historical observations of air temperature during solar eclipses dating back to 1834. The majority of these observations were taken within the paths of totality of total solar eclipses.…”
Section: Radiosondesmentioning
confidence: 99%
See 1 more Smart Citation